Morphogenetic and structural characteristics of xaraes palisadegrass submitted to cutting heights Características morfogênicas e estruturais do capim-xaraés submetido a alturas de corte - Sousa B.M.L. (2011)
The objective of this work was to evaluate the morphogenetic and structural characteristics of xaraes palisadegrass submitted to three cutting heights (15, 20 and 25 cm) when the sward reached 95% of light interception during regrowth. The experiment was carried out according to a complete randomized block design with three replications. The sward surface height under the cutting condition of 95% of light interception was very homogeneous with values around 30 cm. The increase in cutting height reduced the leaf elongation rate and the number of live leaves but increased stem elongation rate. As the cutting criterion was the same, before the intense competition for light, the variation in the cutting severity had a small influence on the morphogenetic and structural characteristics of this grass. In the summer, due to the better growth conditions, the plants presented a higher tissue renewal, which was characterized by a higher leaf elongation rate, reduced leaf lifespan and leaf senescence rate when compared to the other season of the year. Under intermittent defoliation conditions, the regrowth of xaraes palisadegrass can be interrupted at a sward height of 30 cm (frequency) keeping a residual height of 15 cm. © 2011 Sociedade Brasileira de Zootecnia.